(NbRATXQ(B: [(NrOMAN(B];s (NiSPYTANIE ^UWSTW(B: [(NpXESA(B] /s (N~ASTX (B3s - (NfEDIN(B, (NkONSTANTINs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1983)
(Nw NASTOQ]IJ TOM WKL@^ENY ROMAN k(B. (NfEDINA (B"(NbRATXQ(B" (1928), (NA TAKVE PXESA (B"(NiSPYTANIE ^UWSTW(B" (1942) (NI KINOSCENARIJ (B"(NnORWEVCY(B" (1941).s
"(NnORWEVCY(B" (NRASSKAZ DLQ \KRANA(B.s
rus
Keywords: (NpXESYs; (NrOMANs